Isolation and characterization of a proteinaceous antifungal compound from Lactobacillus plantarum YML007 and its application as a food preservative. (29th April 2013) - Ahmad Rather, I.; Seo, B.J.; Rejish Kumar, V.J.; Choi, U.‐H.; Choi, K.‐H.; Lim, J.H.; Park, Y.‐H.
Abstract Korean kimchi is known for its myriad of lactic acid bacteria (LAB) with diverse bioactive compounds. This study was undertaken to isolate an efficient antifungal LAB strain among the isolated kimchi LABs. One thousand and four hundred LABs isolated from different kimchi samples were initially screened against Aspergillus niger. The strain exhibiting the highest antifungal activity was identified as Lactobacillus plantarum YML007 by 16S rRNA sequencing and biochemical assays using API 50 CHL kit. Lact. plantarum YML007 was further screened against Aspergillus oryzae, Aspergillus flavus, Fusarium oxysporum and other pathogenic bacteria. The morphological changes during the inhibition were assessed by scanning electron microscopy. Preliminary studies on the antifungal compound demonstrated its proteinaceous nature with a molecular weight of 1256·617 Da, analysed by matrix‐assisted laser desorption ionization‐time‐of‐flight mass spectrometry (MALDI‐TOF). The biopreservative activity of Lact. plantarum YML007 was evaluated using dried soybeans. Spores of A. niger were observed in the negative control after 15 days of incubation. However, fungal growth was not observed in the soybeans treated with fivefold concentrated cell‐free supernatant of Lact. plantarum YML007. The broad activity of Lact. plantarum YML007 against various food spoilage moulds and bacteria suggests its scope as a food preservative. Significance and Impact of the Study After screening 1400 kimchi bacterial isolates, strain Lactobacillus plantarum YML007 was selected with strong antifungal activity against various foodborne pathogens. From the preliminary studies, it was found that the bioactive compound is a low molecular weight novel protein of 1256·617 Da. Biopreservative potential of Lact. plantarum YML007 was demonstrated on soybean grains, and the results point out YML007 as a potent biopreservative having broad antimicrobial activity against various foodborne pathogens.